Prognostic Awareness and Communication Preferences among Caregivers of Patients with Malignant Glioma - Applebaum, A.J. (Psychooncology, 2017)
OBJECTIVE: Malignant glioma is a devastating neuro-oncologic disease with almost invariably poor prognosis, yet many families facing malignant glioma have poor prognostic awareness (PA), or the awareness of the patient’s incurable disease and shortened life-expectancy. Accurate PA is associated with favorable medical outcomes at the end-of-life for patients and psychosocial outcomes for informal caregivers (ICs) through bereavement. To date, however, no study has specifically examined PA among MG ICs and the information they receive that shapes their awareness. METHODS: Thirty-two ICs of patients with malignant glioma completed a semi-structured assessment of their awareness of the incurability and life expectancy of their loved one’s illness, and to understand their sources of prognostic information and preferences for communication of prognostic information. RESULTS: Twenty two (69%) ICs had full PA - awareness of the incurability of malignant glioma and accurate estimates of their loved ones’ life expectancy. Twenty-three (72%) felt that prognostic information was extremely or very important to possess, and 16 (50%) desired more prognostic information. The majority of ICs received prognostic information from physicians and the Internet. Qualitative analyses revealed that many ICs had difficulty navigating medical encounters in which they concurrently wanted to elicit prognostic information from physicians and protect patients from such information. CONCLUSIONS: Accurate and timely PA is necessary for ICs to serve as critical members of healthcare teams. Interventions are needed to foster ICs’ skills in navigating prognostic communication with patients and healthcare providers and thereby improve their ability to advocate for their loved one’s wishes.